2014
DOI: 10.1093/cid/ciu789
|View full text |Cite|
|
Sign up to set email alerts
|

Is Bacteremic Sepsis Associated With Higher Mortality in Transplant Recipients Than in Nontransplant Patients? A Matched Case-Control Propensity-Adjusted Study

Abstract: The 28-day and 90-day mortality were significantly decreased for transplant recipients compared with nontransplant patients. These findings suggest that the immunosuppression associated with transplantation may provide a survival advantage to transplant recipients with sepsis through modulation of the inflammatory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
91
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(106 citation statements)
references
References 13 publications
12
91
1
2
Order By: Relevance
“…On the other hand, there are recent indirect data against such a practice. Indeed, in two large studies of patients with BSI and sepsis, respectively, the authors observed better outcome among SOT recipients than non‐SOT recipients . A possible explanation for these findings is that immunosuppression following transplantation may attenuate the inflammatory cascade, which is considered one of the main damaging factors of sepsis pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there are recent indirect data against such a practice. Indeed, in two large studies of patients with BSI and sepsis, respectively, the authors observed better outcome among SOT recipients than non‐SOT recipients . A possible explanation for these findings is that immunosuppression following transplantation may attenuate the inflammatory cascade, which is considered one of the main damaging factors of sepsis pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…Renal transplantation that restores renal functions also yields an improvement in immune response. Although all of the renal transplant patients were medicated with many kinds of immunosuppressive agents, it has been shown that morbidity and mortality of severe systemic infections, such as sepsis, have a lower rate in renal transplant patients compared with nontransplant patients [18]. Although MPV was increased in many acute inflammatory and atherothrombotic events, it was also shown that it was decreased in some chronic inflammatory conditions, such as asthma and chronic obstructive pulmonary disease activation [13,19].…”
Section: Discussionmentioning
confidence: 99%
“…18 Interestingly, the study by Aguiar and colleagues 12 showed that use of appropriate empiric antibiotics was associated with increased mortality (6/10 [60%] of deaths vs 7/ 29 [24%] of survivors; P 5 .056) The authors concluded that this paradox was attributable to selection bias, because these patients typically were sicker with higher Charlson comorbidity index and Pitt bacteremia scores. Additionally, Kalil and colleagues 33 in their comparison of mortality owing to bacteremia in transplant versus nontransplant patients found that transplant patients are less likely to receive appropriate antibiotics (84% vs 98%). Presumably this would be owing to presence of resistance among isolates; however, those data were not included.…”
Section: Inappropriate Empiric Antibioticsmentioning
confidence: 99%
“…The 28-day mortality in the SOT group was 78% lower (HR, 0.22; P 5 .001) and 57% lower at 90 days (HR, 0.43; P 5 .25). 33 The other factors in the multivariable hazard model included WBC count, platelet count, elevated heart rate, elevated respiratory rate, Sepsis-related Organ Failure Assessment (SOFA) score, and presence of multiorgan system failure. 33 …”
Section: Morbidity and Mortality Associated With Multidrug-resistant mentioning
confidence: 99%